Postural control performance of active and inactive older adults assessed through postural tasks with different levels of difficulty - Gabriela Vigorito Magalhães; Milena Razuk; Leonardo Araújo Vieira; Natalia Madalena Rinaldi (Universidade Estadual Paulista (UNESP), 2022)
Abstract Aim: To investigate postural control between active (AOA) and inactive (IOA) older adults and active young adults (YA) due to the difficulty level of the postural task. Methods: 25 active YA, 31 AOA, and 30 IOA were invited to perform postural tasks with eyes open and closed: bipedal stance on a rigid surface, bipedal stance on an unstable surface, semi-tandem stance on a rigid surface, and semi-tandem stance on an unstable surface. Results: IOA (0.74 cm) presented higher COP displacement amplitude in the mediolateral direction than AOA (0.64 cm) only in bipedal stance on an unstable surface with eyes closed condition (p ≤ 0.0001). In relation to frequency variables, IOA (0.37 Hz) presented a greater frequency band with 50% of the spectral power in the mediolateral direction than AOA (0.28 Hz) in all experimental conditions, except for semi-tandem stance on a rigid surface (p ≤ .0001). AOA (0.62 cm | 0.28 Hz) and IOA (0.67 cm | 0.37 Hz) presented an increase in time/frequency variables in both directions (anterior-posterior and mediolateral) than YA (0.52 cm | 0.17 Hz) (p ≤ 0.0001) that indicates a worse performance of postural control as the level of task difficulty increased, such as unstable base with eyes open and closed. Conclusion: Older adults tend to present greater COP sway and velocity when subjected to complex tasks compared with younger, which is more evident in older adults physically inactive. This could be considered an adaptive strategy by older adults to minimize the risk of losing balance and, consequently, falling.